The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.micpro.2015.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Composable and predictable dynamic loading for time-critical partitioned systems on multiprocessor architectures

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…On the other hand, update points facets are less discussed facets in the domain.In this study, we have identified a list of 27 models for DSU. Based on the number of primary studies for each model, we list the top five most cited models in Table 11. Furthermore, the result shows other models including binary rewriting [53, 74 ], labelled transition systems [9, 69 ], incremental [83, 102 ], instantaneous [83, 102 ], mix objects object [42, 44 ], dynamic loading [97, 133 ], stack mapping [105 ], adaptation [64 ], aspect‐based [96 ], class‐loading [45 ], dynamic linking [53 ], relocatable code [53 ], event‐based [9 ], multiple consistency [44 ], object space [56 ], dynamic rebinding [5 ], representation consistency [77 ], shared library [53 ], stack reconstruction [74 ], strict consistency [87 ], V‐shape protocol [60 ], state machine [89 ], and component model [70 ]. RQ 3: What programming languages and algorithms employed in dynamic software updating?…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, update points facets are less discussed facets in the domain.In this study, we have identified a list of 27 models for DSU. Based on the number of primary studies for each model, we list the top five most cited models in Table 11. Furthermore, the result shows other models including binary rewriting [53, 74 ], labelled transition systems [9, 69 ], incremental [83, 102 ], instantaneous [83, 102 ], mix objects object [42, 44 ], dynamic loading [97, 133 ], stack mapping [105 ], adaptation [64 ], aspect‐based [96 ], class‐loading [45 ], dynamic linking [53 ], relocatable code [53 ], event‐based [9 ], multiple consistency [44 ], object space [56 ], dynamic rebinding [5 ], representation consistency [77 ], shared library [53 ], stack reconstruction [74 ], strict consistency [87 ], V‐shape protocol [60 ], state machine [89 ], and component model [70 ]. RQ 3: What programming languages and algorithms employed in dynamic software updating?…”
Section: Resultsmentioning
confidence: 99%
“…For DSU time metrics, number of studies have presented various metrics including compile‐time [41, 44, 46, 54, 96 ], load time [41, 45, 60, 133 ], waiting time [51, 73, 76, 83 ], reconfiguration time [59, 60, 62 ], rollback time [51, 101 ], quiescence time [3, 58 ], timeout [9, 111 ], debug time [60 ], disruption time [4 ], down‐time [56 ], garbage collection time [44 ], interrupt time [38 ], synchronisation time [93 ], pausing time [42 ], restart time [60 ], and reconfiguration period [67 ], and warm‐up time [56 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Application bundles contain a description of the required resources and the executable code. These bundles once placed at a specific memory location are processed by the multi-tile loader [17] that instantiates the new application in the running system. In the simulation model, data can be directly placed into the shared memory.…”
Section: B Targeted Hardware Platform and Virtual Equivalentmentioning
confidence: 99%